2014
DOI: 10.4081/ijas.2014.3170
|View full text |Cite
|
Sign up to set email alerts
|

On-Line Monitoring of Milk Electrical Conductivity by Fuzzy Logic Technology to Characterise Health Status in Dairy Goats

Abstract: Intramammary infection affects the quality and quantity of dairy goat milk. Health status (HS) and milk quality can be monitored by electrical conductivity (EC). The aim of the study was to determine the detection potential of EC when measured on-line on a daily basis and compared with readings from previous milkings. Milk yields (MYs) were investigated with the same approach. To evaluate these relative traits, a multivariate model based on fuzzy logic technology -which provided interesting results in cows -wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
1
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 18 publications
(25 citation statements)
references
References 32 publications
0
23
1
1
Order By: Relevance
“…Snapshots and video recordings were acquired every day from the start to the end of a monitoring window. Dates and time stamps were added to each image and used to name each file [32]. Images and video recordings were used in a preliminary phase of the experiment to set up the detection sensor and analyzed in the following phases to evaluate the accuracy of the monitoring system.…”
Section: Methodsmentioning
confidence: 99%
“…Snapshots and video recordings were acquired every day from the start to the end of a monitoring window. Dates and time stamps were added to each image and used to name each file [32]. Images and video recordings were used in a preliminary phase of the experiment to set up the detection sensor and analyzed in the following phases to evaluate the accuracy of the monitoring system.…”
Section: Methodsmentioning
confidence: 99%
“…A high SCC is also linked to a deterioration of milk quality and frequently to a loss in milk production (Gonzalo et al 1994(Gonzalo et al , 2002Ying et al 2002Ying et al , 2004Nudda et al 2003;Leitner et al 2004aLeitner et al , 2004bD€ urr et al 2008;Hagnestam-Nielsen et al 2009;Hand et al 2012). EC is generally used to detect health status, studies in dairy goats showed that daily measurements of EC may represent a useful method to detect intra-mammary infections (D ıaz et al 2012;Zaninelli et al 2014). The electrical conductivity (EC) is one of the indirect systems for determining the quantity of somatic cells in milk (Peris et al 1991;Barth et al 2008;Tangorra et al 2010;Romero et al 2012a).…”
Section: Introductionmentioning
confidence: 99%
“…Although many factors, other than the health status of the mammary gland, can introduce some interpretation errors such as parity, lactation stage, and milk composition [ 22 , 23 , 24 ], the use of this parameter is a well consolidated practice with dairy cows [ 2 , 3 , 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 ] and many devices that evaluate the EC of milk measured in constant current (DC) or alternating current (AC—in a range of frequency between 50–70 kHz) [ 25 ] are available. On the contrary in dairy goats, the use of algorithms and sensors based on the milk EC and included in the milking systems in order to monitor online health status (HS) of the animals is not a widespread practice because of the low performances achieved to date [ 26 , 27 , 28 , 29 ].…”
Section: Introductionmentioning
confidence: 99%
“…The average value of the 20 highest measurements of the gland’s milk EC recorded online during a milking and in case of early lactation, may be used for the monitoring of the animals’ HS [ 28 ]. However, many of these studies suggest the use of more informative indexes built with a better knowledge of the relationship between the milk EC’ signal and the animals’ HS, along with improvements on the algorithms that analyze these data (based on multivariate models), as a possible way to reach good performance detection also in dairy goats [ 26 , 27 , 28 , 29 , 32 , 33 , 34 ].…”
Section: Introductionmentioning
confidence: 99%